2021
DOI: 10.3389/fcimb.2021.781246
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Salivary Mycobiome Diversity in Human Immunodeficiency Virus-Infected Patients

Abstract: Reports on alterations in the oral mycobiome of HIV-infected patients are still limited. This study was designed to compare the salivary mycobiome between 30 human immunodeficiency virus (HIV) infections and 30 healthy controls and explore the effect of antiretroviral therapy (ART) administration on the oral mycobiome of HIV infections. Results showed that the diversity and richness of salivary mycobiome in HIV-infected individuals were higher than those of controls (P < 0.05). After ART, the diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The characteristic fungi in these diseases might be potential fungal markers which could be used to distinguish SLE, RA and UCTDs. Especially, the positive correlation between Archaeorhizomyces and CD4 + T-cell count was found in immune-related diseases ( Chang et al, 2021 ). Although changes in the structure and composition of gut fungi in SLE patients were found in our results compared with RA, CUTDs, and HCs, the relationship of gut fungi with SLE and the biological functions of fungi are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic fungi in these diseases might be potential fungal markers which could be used to distinguish SLE, RA and UCTDs. Especially, the positive correlation between Archaeorhizomyces and CD4 + T-cell count was found in immune-related diseases ( Chang et al, 2021 ). Although changes in the structure and composition of gut fungi in SLE patients were found in our results compared with RA, CUTDs, and HCs, the relationship of gut fungi with SLE and the biological functions of fungi are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They found Candida, Mortierella, Malassezia, Simplicillium, and Penicillium to be significantly increased in HIV-infected individuals and dramatically decreased after ART. In contrast, the abundances of Verticillium, Issatchenkia, and Alternaria were significantly increased in PLWH after ART (27). They found that the composition of the oral mycobiome in the HIV-infected subjects after 6 months of ART was similar to that in the HIV-uninfected individuals.…”
Section: The Oral Mycobiome In Hiv Infectionmentioning
confidence: 97%
“…Moreover, Mortierella , Malassezia , Simplicillium , and Chaetomium were positively associated with viral load (VL), and Verticillium , Thyrostroma and Archaeorhizomyces were negatively associated with VL and positively correlated with CD4 + T-cell counts. In addition, Saccharomyces was positively correlated with VL and negatively associated with CD4 + T-cell counts ( 27 ). Therefore, HIV infection and ART administration might impact on the composition of the oral mycobiome, and the dysbiosis of oral mycobiome in HIV infection could be partially restored after ART.…”
Section: Alterations Of the Mycobiome In Hiv Infectionmentioning
confidence: 99%
“…Limited data have been reported to demonstrate the interkingdom interaction between the virome and mycobiome. However, different alpha and beta diversity of the salivary mycobiome has been observed in individuals with viral infections such as HIV infected individuals [ 102 ]. Nonetheless, to date, only a few studies have addressed the interaction between fungi and viral component of the microbiome and how it affects the host.…”
Section: Crosstalk Between the Virome And Mycobiome And Its Effect On...mentioning
confidence: 99%
“…For example, studies have confirmed the survivability of HSV virus in C. albicans biofilms is due to both decreased accessibility of antivirals to HSV and also the anti-inflammatory environment induced by C. albicans [ 103 , 111 ]. Candida has also been reported to be abundant in HIV-positive individuals, but without a statistical difference from HIV-negative persons [ 102 ]. Furthermore, increased abundance of adenoviruses and anelloviruses has been reported in fecal samples of HIV-positive individuals with low CD4+ T-cell counts [ 112 ].…”
Section: Crosstalk Between the Virome And Mycobiome And Its Effect On...mentioning
confidence: 99%